2010
DOI: 10.1111/j.1469-0691.2010.03156.x
|View full text |Cite
|
Sign up to set email alerts
|

Close cooperation between infectious disease physicians and attending physicians can result in better management and outcome for patients with Staphylococcus aureus bacteraemia

Abstract: Staphylococcus aureus bacteraemia (SAB) is a serious infection that demands prompt clinical attention for good outcome. To assess the impact of intervention by infectious diseases physicians (IDPs) in cases with SAB, a retrospective cohort study of patients with SAB was performed in a 1240-bed, university hospital in Japan, with the aim of comparing the management and outcome of patients during the initial and the latter half of the intervention period,. Three hundred and forty-six patients with SAB during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 22 publications
1
41
0
2
Order By: Relevance
“…All found clinical benefit; 11 reported improved mortality among patients who received IDC. 8393 IDC was also associated with increased adherence to standards of care, including selection of a β-lactam for MSSA infections, 8488,94,95 longer duration of therapy for complicated infection, 8388,92,94,95 removal of intravenous catheters, 84,94 obtaining follow-up blood cultures to assess for clearance of bacteremia, 84,85,87,88,9294 obtaining echocardiography, 83,85,86,88,93,96 draining abscesses, 84 and removing infected prosthetic material. 84,95 Thus, while the evidence for routine IDC in patients with SAB is limited to observational studies, it supports the conclusion that IDC should be considered for every case of SAB at institutions where such expertise is available.…”
Section: Discussionmentioning
confidence: 99%
“…All found clinical benefit; 11 reported improved mortality among patients who received IDC. 8393 IDC was also associated with increased adherence to standards of care, including selection of a β-lactam for MSSA infections, 8488,94,95 longer duration of therapy for complicated infection, 8388,92,94,95 removal of intravenous catheters, 84,94 obtaining follow-up blood cultures to assess for clearance of bacteremia, 84,85,87,88,9294 obtaining echocardiography, 83,85,86,88,93,96 draining abscesses, 84 and removing infected prosthetic material. 84,95 Thus, while the evidence for routine IDC in patients with SAB is limited to observational studies, it supports the conclusion that IDC should be considered for every case of SAB at institutions where such expertise is available.…”
Section: Discussionmentioning
confidence: 99%
“…Minimization of SSI can be achieved by refinement of surgical technique 8 and direct consultation by infectious disease physicians. 16,28 Because the majority of gram-positive Enterococci and gram-negative rods in our center were previously reported to be resistant to flomoxef, which was used for postoperative prophylaxis in our center, broaderspectrum prophylaxis, if implemented, should be reassessed continually with respect to the potential for emergence of increasing antimicrobial resistance (to the prophylactic agents used). 20,29,30 Initial reports from our center and others 7,8,20,23,25,27 indicated that Candida was the most common fungal infection after LT. Those results are in accordance with our present study results.…”
Section: Discussionmentioning
confidence: 99%
“…obtaining an echocardiograph (69,81,83,85,87,88), (iii) removing infected foci (80,86,89), (iv) providing a longer duration of treatment for complicated SAB (80)(81)(82)(83)(84)(86)(87)(88)(89), and (v) administering ␤-lactam antibiotics for MSSA infections (80,81,83,86,88,89). Eleven studies also reported that ID consultation for SAB is associated with reduced patient mortality rates (61, 62, 80-85, 87, 88, 90).…”
Section: Outcomes and Managementmentioning
confidence: 99%
“…An infectious diseases (ID) consultation can play a key role in facilitating the process of appropriate investigation and management of patients with SAB. ID consultation for patients with SAB is associated with higher rates of various quality-of-care metrics, including (i) obtaining follow-up blood cultures to assess the clearance of SAB (80)(81)(82)(83)(84)(85)(86), (ii) a The mean percentages of patients for each primary focus of infection from all the studies were as follows: 5% for infective endocarditis, 8% for osteoarticular, 19% for SSTI, 9% for pleuropulmonary, 26% for line related, 24% for no focus/unknown, and 11% for other foci. MRSA, methicillin-resistant S. aureus; HCA, health care associated; SSTI, skin and soft tissue infection.…”
Section: Outcomes and Managementmentioning
confidence: 99%